(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Glass is one of the most common materials in medicine. It is used due to being biologically inert, having excellent optical transparency and possibility to handle it easily. However, there are severe limitations in processing glass structures in 3D fashion at µm scale. In this work we present femtosecond laser-based selective glass etching as an attractive tool to produce medical glass structures. We discuss how it can be used to create various microfluidical and micromechanical systems. The challenges and capabilities related to the technology are highlighted, comparing it to other additive manufacturing techniques.